2,4-Dihydroxybenzaldehyde 4-ethylthiosemicarbazone - Tan, Kong Wai; Ng, S.W.; Maah, Mohd Jamil; Ng, C.H. (International Union of Crystallography, 2008)
The molecular conformation of the title compound, C(10)H(13)N(3)O(2)S, is stabilized by an intramolecular O-H center dot center dot center dot N hydrogen bond. Adjacent molecules are linked by O-H center dot center dot center dot O hydrogen bonds to furnish a zigzag chain.